Issues & Observations : Improving Performance Through Flexible Leadership - Yukl, Gary; Lepsinger, Richard (Center for Creative Leadership, 2005)
In most industries there are companies that consistently outperform competitors that have similar business strategies and operating models and must deal with the same economic conditions. The key factor in explaining the difference in long-term performance for these firms is the quality of leadership.